Our system is currently under heavy load due to increased usage. We're actively working on upgrades to improve performance. Thank you for your patience.
2023
DOI: 10.33417/tsh.1266417
|View full text |Cite
|
Sign up to set email alerts
|

Kurum Bakımında ve Ailesiyle Yaşayan Ergenlerin Bağlanma, Sorumluluk ve Kaygı Düzeyleri Arasındaki İlişki

Ruveyda TAŞKAYA,
Arzu ÖZYÜREK

Abstract: Bireyin gelişiminde, birincil çevresini oluşturan ve en önemli desteği sağlayan aile kurumudur. Aile desteğinden yoksun olarak kurum bakımında kalmak, bireyi farklı düzeylerde etkileyebilir. Bu çalışmada, kurum bakımında ve ailesiyle birlikte yaşayan ergenlerin bağlanma stili, sorumluluk duygu ve davranışları ile kaygı durumlarının belirlenmesi; bağlanma, sorumluluk ve kaygıları arasındaki ilişkinin incelenmesi amaçlanmıştır. Çalışmanın örneklemini 380 ergen oluşturmuştur. Verilerin toplanmasında Üç Boyutlu Ba… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2024
2024
2024
2024

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(2 citation statements)
references
References 15 publications
0
2
0
Order By: Relevance
“…Therefore, the insecure attachment relationships that children establish with their primary caregivers or the effects of the separation they experience with their primary caregivers negatively affect the attachment relationships they develop later. Several studies have frequently reported that people who experience separation from their primary caregivers develop insecure attachment relationships (Katz 2003, Schleiffer and Müller 2004, Katsurada 2007, Üstün 2008, Şahin 2009, Torres et al 2012, Karakoyun 2015, Subaşı 2015, Ayanoğlu Yüksel 2016, Howard et al 2017, Yüceer Kardeş 2018, Yıldız 2019, Taşkaya 2019. Indeed, a person may experience loss and grief in childhood, which they will inevitably encounter throughout their life.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Therefore, the insecure attachment relationships that children establish with their primary caregivers or the effects of the separation they experience with their primary caregivers negatively affect the attachment relationships they develop later. Several studies have frequently reported that people who experience separation from their primary caregivers develop insecure attachment relationships (Katz 2003, Schleiffer and Müller 2004, Katsurada 2007, Üstün 2008, Şahin 2009, Torres et al 2012, Karakoyun 2015, Subaşı 2015, Ayanoğlu Yüksel 2016, Howard et al 2017, Yüceer Kardeş 2018, Yıldız 2019, Taşkaya 2019. Indeed, a person may experience loss and grief in childhood, which they will inevitably encounter throughout their life.…”
Section: Discussionmentioning
confidence: 99%
“…Indeed, these studies revolutionized children's attachment-separation and grief processes by revealing significant findings that separation and maternal deprivation negatively affect the development of infants and children. Later, studies with children in institutional care and adults who experienced institutional care during childhood indicated that separation from the primary caregiver and being deprived of their attention, care, and love had adverse psychological, social, and behavioral effects (Yılmaz 2005, Cross and Purvis 2008, Şimsek et al 2008, Şimsek et al 2008, Muguwe 2012, McLaughlin et al 2015; in addition, people who had this experience commonly develop insecure attachment relationships (Katz 2003, Schleiffer and Müller 2004, Katsurada 2007, Üstün 2008, Şahin 2009, Torres et al 2012, Karakoyun 2015, Subaşı 2015, Ayanoğlu Yüksel 2016, Howard et al 2017, Yüceer Kardeş 2018, Yıldız 2019, Taşkaya 2019) and supported the results of these studies.…”
Section: Separation Anxietymentioning
confidence: 99%